(untitled) (The Journal of Medicine, Humanity and Media, 2024)
On the afternoon of July 9, 2024, panel 3 of the 7th "Medicine, Humanity, and Media" International Conference: Health Communication Strategies and Methods for At-Risk Populations was held in Lecture Hall 113 at the School of Journalism and Communication, Peking University. Associate Professor Jung Younbo from the Wee Kim Wee School of Communication and Information at Nanyang Technological University and Assistant Professor Jiang Shaohai from the Department of Communication and New Media at National University of Singapore served as discussants. Seven authors, Li Zhangyan from Zhejiang University, Wu Qiudi from Shenzhen Polytechnic University, Gou Linxuan from China Agricultural University, Chen Yanshan from Soochow University, Liu Qian from Jinan University, Zhao Yitong from East China Normal University, and Xian Xuechang from Zhaoqing University presented their findings.